2018
DOI: 10.15408/kauniyah.v11i1.5662
|View full text |Cite
|
Sign up to set email alerts
|

MORFOLOGI PERMUKAAN DAUN TANAMAN TERUNG (Solanum melongena L.) SEBAGAI RESPONS TERHADAP CEKAMAN KEKERINGAN

Abstract: Terung (Solanum melongena L.) tergolong tanaman yang sensitif terhadap kekeringan selama tahap pertumbuhan dan perkembangannya. Karakteristik stomata dan trikoma merupakan kriteria yang dapat digunakan untuk mengidentifikasi tanaman yang toleran terhadap kekeringan. Penelitian bertujuan menguji respons karakteristik anatomi daun berupa trikoma dan stomata tanaman terung terhadap cekaman kekeringan melalui empat taraf interval penyiraman. Penelitian menggunakan Rancangan Acak Lengkap melalui empat taraf interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Trichome density ranged from 1.59 -4.62 mm -2 . According to the increasing number of trichomes, it can provide advantages, including protecting the tissue from damage and reducing over-transpiration [35]. The grouping results showed that there were four accession groups based on morphophysiological characters.…”
Section: Anatomymentioning
confidence: 99%
“…Trichome density ranged from 1.59 -4.62 mm -2 . According to the increasing number of trichomes, it can provide advantages, including protecting the tissue from damage and reducing over-transpiration [35]. The grouping results showed that there were four accession groups based on morphophysiological characters.…”
Section: Anatomymentioning
confidence: 99%
“…The presence of drought stress can increase the density of trichomes. Ilahi et al (2018), in his research, explained that it was increasingly difficult for eggplant (Solanum melongena L.) to absorb water from the soil due to the long watering interval, resulting in an increase in the number of trichomes in one field of view. The increase in the number of trichomes is inversely proportional to their smaller size.…”
Section: Epidermal Characteristics and Epidermalmentioning
confidence: 99%
“…Pada setiap plot sampel tumbuhan diambil berdasarkan ketianggian tumbuhan yang relatif sama dan tidak terkena penyakit pada setiap daerah. Pengambilan sampel untuk anatomi kerapatan stomata menggunakan modifikasi metode Ilahi et al (2018) Hasil pengukuran respons anatomi meliputi kerapatan stomata, ketebalan epidermis dan ketebalan palisade pada tumbuhan A. muelleri Blume pada lokasi yang berbeda dipengaruhi oleh ketinggian tempat. Apabila ketinggian tempat berbeda maka tumbuhan akan memberikan perbedaan respons pertumbuhan baik morfologi maupun anatomi.…”
Section: Bahan Dan Metodeunclassified